AB0692 Radiographic Damage in A Group of Patients with Axial Spondyloarthritis. (10th June 2014) - Toniolo, E.; Laiz, A.; Moya, P.; Díaz-Torné, C.; Castellvi, I.; Geli, C.; Sarmiento, M.; Millán, A.M.; Llobet, J.M.
Abstract : Background: Recent studies in the field of axial spondyloarthropathies (SpA-ax) have shown a group of patients with chronic lower back pain without evidence of radiographic damage (non-radiographic axial spondyloarthritis). Currently, data is lacking that would confirm whether it is an early stage of the disease or a group of SpA-ax that is different, in which time of progression and radiographic damage show no relationship. Objectives: Describe our cohort of patients diagnosed with radiographic axial spondyloarthritis. Assess whether those with both sacroiliac and spinal radiographic involvement have a longer duration of the disease and the relationship between this most-affected group and the different items that constitute the ASAS criteria for SpA-ax. Methods: All patients diagnosed with SpA-ax by ASAS or NY criteria, who were seen in a monographic consultation of spondyloarthritis of our center between January 2012 and December 2013, were reviewed. Only those with sacroiliitis of grade II or higher were included; patients who did not have spinal radiographs were excluded. The following clinical and laboratory variables were collected from clinical history: age, sex, duration of disease, inflammatory back pain, arthritis, enthesitis, uveitis, dactylitis, psoriasis, inflammatory bowel disease, positive response to NSAIDs, family history of SpA, HLA-B27 and elevated CRP. The presence of 3 or more syndesmophytes in the dorsal and/or lumbar region was considered as spinal involvement. For statistical analysis, student's t-test, chi-square test or Fisher's exact test were performed where applicable. Results: Of the 72 patients diagnosed with SpA-ax, 58 met the inclusion and exclusion criteria. The mean age of the study patients was 53.69 years and 69% were men. The mean disease duration was 19.48 years and 36 patients had spinal involvement. Only the age of patients, the sex and the duration of the disease showed significant results regarding the structural damage (see table). Conclusions: In our cohort, patients with more severe radiographic involvement were those of a longer disease duration and an older age, with a predominance of men. No significant differences for the remaining assessed variables were found, including signs of inflammation and HLA-B27, which were similar in both groups of patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4483